1986
DOI: 10.1111/j.1365-2230.1986.tb00520.x
|View full text |Cite
|
Sign up to set email alerts
|

Visual and cutaneous toxicity which occurs during N-(4-hydroxyphenyl) retinamide therapy for psoriasis

Abstract: Summary Vitamin A (retinol) has been used both topically and systemically in the treatment of skin disease for approximately 40 years (Berson, 1983). Retinol taken in high doses over a period of time can cause fatigue, headaches, cheilitis, anorexia, peeling of the skin and can cause papillary oedema and hepatotoxicity (Dahl et al., 1977). These symptoms form the hypervitaminosis A syndrome and can be caused by acute or chronic intoxication with vitamin A or vitamin A analogues (retinoids). Because of this tox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Ceramides and ceramide metabolism have been implicated in DENV replication (32) and DENV-induced apoptosis (33)(34)(35), making 4-HPR an attractive antiviral molecule that interacts with known lipid pathways important for DENV infection. Additionally, 4-HPR has been investigated in the clinic as a potential treatment or preventative agent for various cancers (36,37), psoriasis (38), obesity-associated insulin resistance (39), and macular degeneration (40). The known safety and bioavailability profiles of 4-HPR therefore make it an attractive candidate for repurposing as an antiviral agent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ceramides and ceramide metabolism have been implicated in DENV replication (32) and DENV-induced apoptosis (33)(34)(35), making 4-HPR an attractive antiviral molecule that interacts with known lipid pathways important for DENV infection. Additionally, 4-HPR has been investigated in the clinic as a potential treatment or preventative agent for various cancers (36,37), psoriasis (38), obesity-associated insulin resistance (39), and macular degeneration (40). The known safety and bioavailability profiles of 4-HPR therefore make it an attractive candidate for repurposing as an antiviral agent.…”
Section: Resultsmentioning
confidence: 99%
“…The molecular targets of 4-HPR relevant to cancer (36,37), macular degeneration (40), psoriasis (38), obesity-associated insulin resistance (39), and other diseases are still elusive, despite considerable investigation over the previous decades. A recurring theme complicating these studies has been the polypharmacology of 4-HPR.…”
Section: Discussionmentioning
confidence: 99%
“…[136][137][138][139][140][141] The usual manifestations of blepharoconjunctivitis include dry eyes, blurred vision, and intolerance of contact lenses. Blackman et al reported blepharoconjunctivitis in 42 of 97 patients receiving isotretinoin.136 Symptoms and signs disappeared within a week after discontinuation of therapy.…”
Section: Miscellaneous Drugs Retinoidsmentioning
confidence: 99%
“…Initial clinical studies with 4-HPR at high doses (Kingston et al, 1986;Kaiser-Kupfer et al, 1986) were hampered by the fact that it has profound effects on the normal metabolism of vitamin A. It has been demonstrated that the regulation of RBP is greatly affected both in humans and experimental animals treated with 4-HPR (Formelli et al, 1987(Formelli et al, , 1989.…”
mentioning
confidence: 99%